Pemberdayaan Wanita Pekerja Seks (WPS) Melalui Peer Educator (Upaya Pencegahan Infeksi Menular Seksual dan HIV/AIDS di Kota Cirebon) - Nur Rahman; Dewi Kusuma Elya; Giyono Urip; Tamsik Udin (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
Based on data obtained from the Cirebon City AIDS Commission (KPA), people living with HIV/AIDS (PLWHA) in Cirebon City until December 2022 amounted to 2,491 people. The number of PLWHA in Cirebon City from year to year the trend is increasing. One of the efforts to prevent and control STIs and HIV/AIDS among female sex workers is by empowering Peer Educators (PE). They are former sex workers who care about their friends by socializing the dangers of STIs and HIV/AIDS. In addition, PEs who already have life skills will share their experiences with female sex workers. The method used in this PKM is the participatory approach method. The PKM process is expected to be able to bring changes to the FSW group in Cirebon City.